The sneaky snails. - Jacobs, Jaco; Van Houwelingen, Alex; van der Molen, Melinda (Midrand; LAPA publishers, 2016)
Mrs Longbottom s garden is full of snails. Huge, slimy snails! Zack and Vincent decide to help. They catch the snails. It s loads of fun! And they even get a reward for the hard work. Mrs Longbottom bakes them some delicious cookies. But Brett the Bully wants to eat all the cookies .
Keywords: Children's stories; Readers (Primary); Readers (Elementary) -- South Africa; Bullying; Friendship